Surgical efficiency in bilateral cochlear implantation: A cost analysis. (January 2014) - Merdad, M; Wolter, NE; Cushing, SL; Gordon, KA; Papsin, BC
Abstract : Objective: (1) Compare the non-device-related costs of bilateral simultaneous cochlear implantation (BSiCI) vs. unilateral, and (2) establish a dollar amount for potential cost savings in direct costs for BSiCI vs. sequential cochlear implantation (CI). Methods: Data from all CI cases performed during the fiscal year 2010–2011 were retrospectively reviewed without exception. Fifty-four patients received unilateral CI and 36 received BSiCI. Demographics and data regarding direct costs associated with the operation and immediate in hospital post-operative period were collected. Results: The total operating room (OR) time for unilateral and BSiCI was 3 hours 00 minutes and 4 hours 37 minutes, respectively, with a mean difference of 1 hour and 36 minutes (SD = 0 hours:06 minutes). The cost of OR and post-anesthetic care unit supporting staff was $3102 and $4240 for unilateral and BSiCI, respectively, with a mean difference of $1138 (SD = 216). Unilateral CI supplies totaled $1348 compared to $1822 for BSiCI supplies with an average difference of $438 (SD = 123). Conclusion: The total direct costs for a unilateral CI (excluding implantable device and surgeon fees) were $4362 compared to $5823 dollars for BSiCI. Simultaneous implantation can lead to a potential saving of $2901 compared to sequential implantation.